Impacto da desigualdade de riqueza nas emissões de CO2 - Warnava, Elvis Giovani (2020)
The present work aims to analyze the impact of wealth distribution on CO2 emissions. The main hypothesis is the suposition that power from economic earnings produce groups that use mechanisms to impose the environmmental costs on less afluent individuals. To achieve this objective it will be explained the main theoretical concepts present in literature, also others approaches that helps to understand the association between economic distribution and environmental impact. Lastly to implement the dynamic Arellano-Bond model of panel data the work aims to verify if the hypothesis is consistent to high-income countries and also to non-high-income countries. According to the results the aproach is consistent for high income countries, however, possibly because of lack of data and institutional specificities on the second group the hyposhesis is not proper. For high-income countries the results are obtained from a sample of 27 countries from 2000 to 2014, for non-high-incomes the sample available has 16 countries for the same period.